PENGARUH PENGHAPUSAN LAYANAN FREE BAGGAGE ALLOWANCE OLEH MASKAPAI LION AIR TERHADAP KEPUASAN PELANGGAN DI BANDAR UDARA INTERNASIONAL AHMAD YANI SEMARANG - Elsa Oktian Sari Utomo; Ahmad Musadek; Siti Fatimah (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Due to the increasing demand of the flight services, many airlines are competing to improve the quality and image of their companies. For this reason,the airlines must know what service the passengers want, because the level of service provided by the airline will affect the level of passenger’s satisfaction to the service. By carrying out the Low Cost Carrier concept or low-cost airline, Lion Air conveyed its new policy, it was removing the Free Baggage Allowance service. The provisions of the luggage and baggage all domestic consist of the Lion Air flights which do not receive free baggage of 20 kg per passenger. Also, all domestic Wings Air flights are not get free of charge of 10 kg per passenger. That is, the checked baggage for passengers will be charged, from the previously free. With the application of the policy , the pros and cons appeared in the community especially the customer and prospective customers to Lion Air airline. The research method applied is quantitative descriptive with reference to the International Air Transport Association (IATA) Resolution No. 302/2011 and PM 185 of 2015 about "THE STANDARDS OF ECONOMIC CLASS SERVICE QUALITY FOR THE SCHEDULED DOMESTIC AIR TRANSPORTATION PASSANGERS ". The method of data collection uses the method of observation, questionnaires and literature studies. The result of this research program is that the removal of free baggage allowance program has effected to the customer satisfaction as much as 32,3 % , in addition customer satisfaction is also influenced by the quality of the services provided by the Airlines as much as 67,7%